Pendampingan UMKM dalam Pemasaran dan Pembukuan Keuangan sebagai Upaya Mengakses Pembiayaan Bank Syariah - Mita Anggraini; Suci Permata Sari; Kharyn Rahmelia; Nurul Hak; Yenti Sumarni (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
MSME actors in Indonesia still face various obstacles in business management, especially in the aspects of marketing and financial bookkeeping. This condition has a direct impact on the low level of bankability of MSMEs to access financing from banking institutions, especially Islamic banks. This activity aims to provide assistance to MSME actors, especially Toko Cipta Swara Elektronik, to be able to prepare basic financial statements and implement simple digital marketing strategies. The method used in this activity is the ABCD (Audience, Behavior, Condition, Degree) approach, with the implementation in the form of lectures, discussions, hands-on practice, and simulations. The results of the activity show that partners are able to prepare two types of basic financial statements (cash flow and profit and loss), design digital marketing strategies through social media, and understand the requirements for applying for Islamic bank financing. This assistance has proven to be effective in increasing the capacity of partners administratively and strategically, as well as opening up greater opportunities to access sharia financing services.